2023
DOI: 10.1111/cpr.13578
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the interaction between m6A modification and lncRNA in cancer drug resistance

Yizhou Jin,
Zhipeng Fan

Abstract: Drug resistance is perhaps the greatest obstacle in improving outcomes for cancer patients, leading to recurrence, progression and metastasis of various cancers. Exploring the underlying mechanism worth further study. N6‐methyladenosine (m6A) is the most common RNA modification found in eukaryotes, playing a vital role in RNA translation, transportation, stability, degradation, splicing and processing. Long noncoding RNA (lncRNA) refers to a group of transcripts that are longer than 200 nucleotides (nt) and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 206 publications
0
3
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are >200 bp RNAs that do not encode proteins, which have been demonstrated to fully participate in the metabolic processes of cancer cells ( 1 ). Compared with RNA-encoding proteins, lncRNAs possess a greater reservoir of transcriptional information ( 2 ). EGFR-AS1 is a 2,821-kb lncRNA located on human chromosome 7; its locus is in the opposite direction of EGFR gene transcription according to the UCSC database ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are >200 bp RNAs that do not encode proteins, which have been demonstrated to fully participate in the metabolic processes of cancer cells ( 1 ). Compared with RNA-encoding proteins, lncRNAs possess a greater reservoir of transcriptional information ( 2 ). EGFR-AS1 is a 2,821-kb lncRNA located on human chromosome 7; its locus is in the opposite direction of EGFR gene transcription according to the UCSC database ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported interactions between m 6 A modifications and lncRNAs ( Ma et al, 2019 ; Yi et al, 2020 ). m 6 A modifications affect the functions of lncRNAs through an m 6 A-switch, thereby inhibiting transcription, mediating competing endogenous RNA (ceRNA) effects, and regulating lncRNA stability or degradation ( Jin and Fan, 2023 ; Mehrdad et al, 2023 ); for example, METTL14-mediated m 6 A methylation and TINCR lncRNA regulation in pyroptosis and diabetic cardiomyopathy ( Meng et al, 2022 ). The combination of the m 6 A reader YTHDC1 and lncRNA XIST promotes lncRNA XIST -mediated gene repression ( Patil et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of the mechanisms underlying the interaction between m 6 A modifications and lncRNAs, an increasing number of studies have investigated their potential applications in the diagnosis, prognosis, and treatment of tumors and determining the sensitivity of cancer cells to chemotherapeutic agents ( Jin and Fan, 2023 ). A previous study accurately predicted the 5-year survival of patients with GC by stratifying their overall survival (OS) using a risk prediction model based on 11 m 6 A-associated lncRNAs ( Wang H et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%